Exploring disintegration and swelling dynamics in Kappa-Carrageenan-based seaweed capsule shells - Maya Soraya; Hendrawan Laksono; Renny Primasari Gustia Putri; Ida Royanti; Dayu Dian Perwatasari; Rizky Aulia Prasasti Dewi; Heri Purwoto (South African Journal of Chemical Engineering)
Kappa-Carrageenan or κ-Carrageenan-based seaweed capsule shells offer an appealing option for pharmaceutical formulations, particularly for vegetarian preferences. However, their disintegration kinetics present challenges for efficient medication release. This study investigates the disintegration dynamics of seaweed capsules, focusing on the swelling mechanism and the influence of various disintegrants. κ-Carrageenan-based capsule shells incorporating Polyvinylpyrrolidone, Primogel, Croscarmellose sodium, and Sodium Carboxymethylcellulose were examined for swelling behavior and disintegration time. Results reveal deviations in swelling behavior, with added disintegrants altering the disintegration mechanism towards wicking. Notably, Primogel demonstrates a significant wicking mechanism effect, evidenced by its markedly lower swelling value compared to other disintegrants (949.944 %). Analysis of swelling kinetic parameters further elucidates distinct trends in the swelling behavior of capsules containing different disintegrants, suggesting that Primogel promotes a gradual water uptake, facilitating wicking within the capsule matrix. Furthermore, capsules with Primogel exhibit the lowest disintegration time among tested disintegrants, achieving 36 min and 21 s. The study also explores the impact of disintegrants on capsule shell coloration and surface morphology, crucial factors influencing consumer acceptance. In conclusion, the study underscores the relationship between swelling propensity and disintegration time, providing valuable insights for optimizing capsule formulations in pharmaceutical applications.